American Pop Art (New York : Whitney Museum of American Art, 1974)
Artschwager, Richard ; Bengston, Billy Al ; D'Arcangelo, Allan ; Dine, Jim ; Goode, Joe ; Hefferton, Philip ; Indiana, Robert ; Johns, Jasper ; Lichtenstein, Roy ; Oldenburg, Claes ; Ramos, Mel ; Rauschenberg, Robert ; Rivers, Larry ; Rosenquist, James ; Ruscha, Edward ; Warhol, Andy ; Wesselmann, Tom
American Pop Art, Whitney Museum of American Art, New York, April 6 - June 16, 1974
boek
Keywords: Amerika